Historically underrepresented students: influences of rurality, parent education level and family income on graduate school intentions - Sexton, Kody K.; Gibbons, Melinda M.; Hardin, Erin E.; Cook, Katherine D.; Hoch, Jess; Ault, Haley R. (Frontiers in Education, 2025)
IntroductionDespite increasing rates of graduate school attendance, students from historically underrepresented backgrounds enroll in graduate programs at lower rates than their peers. Although there is a growing body of research on current graduate students' perspectives on what impacted their decision to pursue graduate education, few studies have examined the intention to pursue graduate education specifically among second- and third-year undergraduate students from first-generation, rural, and/or low-income backgrounds.MethodOur study investigated the predictive roles of self-efficacy, outcome expectations, mentoring, and belongingness on students' intentions to pursue graduate education. Participants included 179 undergraduate students who were low-income, rural, and/or from a first-generation background. Participants completed online surveys to answer the research questions related to social cognitive beliefs and graduate school intentions.ResultsOnly the two social cognitive variables, self-efficacy and outcome expectations, emerged as significant predictors of graduate school intention. Belongingness and mentoring did not significantly impact graduate education intentions. Participants who identified as rural, low-income, and first-generation had lower mentoring support scores compared to their peers. Participants with higher graduate school self-efficacy and outcome expectations demonstrated higher graduate school intentions.DiscussionThe results suggest that social cognitive variables, specifically graduate school self-efficacy and outcome expectations, impact graduate school intentions in underrepresented college students. Also, the additive effects of multiple marginalized identities appears to negatively impact beliefs about attending graduate school. Therefore, Social Cognitive Career Theory can be a powerful tool in helping rural, first-generation, and low-income students increase their beliefs about being able to successfully attend and complete graduate school. Focusing on these social cognitive variables may help increase the number of students from these historically excluded backgrounds to pursue more schools after their undergraduate career.